SUSTAINABLE URBAN TRANSPORTATION: PROGRESS AND POTENTIAL IN SARAWAK - Zainordin, Nadzirah; Abidin, Muhd (PEOPLE: International Journal of Social Sciences, 2017)
The quality of transportation service it’s a main factor to increase the level of economic and social in Sarawak. By increasing the system may buzz-up all sector and may contribute the benefit to the community. This research will be conducting in four selected locations consist of Sibu, Miri, Bintulu and Kuching. The reason to choose these four locations it’s because of the role that each location plays in contributing to the economic sector in Sarawak state itself. Methodology to be used to conduct this research its quantitative method. Where, 300 set of questionnaire to be distributing to the stated locations to get a perception on the concept of sustainable transportation among respondents. Questionnaire distributing to those who has knowledge towards sustainable transportation and it’s limited to those who have experience in construction sector only. The objectives of this research it’s to investigate the construction player’s perception towards sustainability transportation in Kuching, Miri, Bintulu and Sibu; and to identify the barriers factor to implementing this concept. Expecting distribution from this research it’s to create awareness by implementing this concept it’s beneficial to the routine activities as well as can generate and increase the Sarawak’s economic sector.